Overexpression of SOD-2 reduces hippocampal superoxide and prevents memory deficits in a mouse model of Alzheimer's disease - Massaad, Cynthia A. (National Academy of Sciences, 2009)
Alzheimer's disease (AD) is a neurodegenerative disease characterized by impaired cognitive function and the deposition of extracellular amyloid plaques and intracellular tangles. Although the proximal cause of AD is not well understood, it is clear that amyloid-β (Aβ) plays a critical role in AD pathology. Recent studies also implicate mitochondrial abnormalities in AD. We investigated this idea by crossing mice that overexpress mitochondrial superoxide dismutase (SOD-2) with the Tg2576 mouse model of AD that overexpresses the human amyloid precursor protein carrying the Swedish mutation (K670N:M671L). We found that overexpression of SOD-2 decreased hippocampal superoxide, prevented AD-related learning and memory deficits, and reduced Aβ plaques. Interestingly, SOD-2 overexpression did not affect the absolute levels of Aβ(1–40) and Aβ(1–42), but did significantly reduce the Aβ(1–42) to Aβ(1–40) ratio, thereby shifting the balance toward a less amyloidogenic Aβ composition. These findings directly link mitochondrial superoxide to AD pathology and demonstrate the beneficial effects of a mitochondrial anti-oxidant enzyme, hence offering significant therapeutic implications for AD.